Comparison of design methods for steel silos - Pichugin, Sergii; Oksenenko, Kateryna (Academic journal Industrial Machine Building Civil Engineering, 2022)
The article describes the types of silos depending on the wall design. A review of the standard documents that are in force on the territory of Ukraine and regulate the determination of loads and forces in silos is carried out. The differences between the calculations of horizontal and vertical pressures on the walls of silos according to DBN B2.2-8-98 Enterprises, buildings and structures for grain storage and processing and DSTU-N B EN 1991-4:2012 Eurocode 1: Actions on structures – Part 4: Silos and tanks were analyzed. The design formulas for defining pressures according to two standards are given. The spreads of statistical properties of particulate solids are analyzed. The normative horizontal pressure and vertical frictional pressures for a flexible silo were calculated according to two standards. Graphs of horizontal and vertical pressures of particulate solids material on the walls of a flexible silo are presented. According to the calculations, it is concluded that the spreads of statistical properties of particulate solids has a significant impact on the magnitude of loads on the vertical walls of silos. It is noted that the value of the wall friction coefficient has a significant impact on the calculation of horizontal pressure
Keywords: silo; horizontal pressure; vertical pressure; friction forces; particulate solids